Study of cathodic protection shielding under coating disbondment on pipelines. (October 2015) - Kuang, Da; Cheng, Y. Frank
Highlights: Investigated the permeability of pipeline coatings to cathodic protection. Studied corrosion of steel under disbonded coating. Monitored in-situ the pH of the electrolyte trapped under coating. Illustrated the mechanism of the compatibility of pipeline coatings with cathodic protection. Abstract: In this work, the cathodic protection (CP) shielding behavior of pipeline coatings, i.e., high density polyethylene (HDPE) and fusion bonded epoxy (FBE), was investigated. While the HDPE is a CP-shielding coating, the FBE is permeable to CP. The structure of HDPE does not change upon CP permeating test, and water molecules are not absorbed into the coating. Conversely, there are obvious changes of the functional groups in FBE. Water uptakes into the coating occur continuously with time. The CP permeation through FBE coating is time dependent. A more negative CP potential level enhances the CP permeation.